Nacionalni in komercialni radio - jezikoslovčev pogled na radijski jezik - Valh Lopert, Alenka (Teorija in praksa, 2009)
This article presents the results of a study of a spoken corpus comprising broadcasts by the national radio station, Radio Maribor, and the commercial station, Radio City (Maribor). The study is based on the assumption that radio language is dependent on the linguistic and communicative skills of professional presenters, while code-switching is largely dependent on purpose and circumstances. The stratification of media language reflects a need for identification with the language of the surroundings in direct speech, and a need for standard language for wider communication (in reported speech). The article presents the (1) morphological and (2) lexical features typical of the regional vernacular displayed by the broadcasters at both radio stations (according to Slovenski pravopis/the Slovene Orthographic Manual 2001).
Keywords: Slovene; Slovenian language; Slovenščina; Jezikovna kultura; Culture of language; Govor; Speech; Slovenija; Radio; mass media; množični mediji; Slovenia; radijski govor; govorna kultura; Radio Maribor; Radio City